The Main Aspects of Enterprise Competitiveness - Szymanik, Ewa (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The article examines the theoretical aspects of enterprise competitiveness, reviewing the contemporary definitions of such competitiveness and looking at one of the author’s own design. It also discusses the main aspects and determinants of competitiveness. The conclusions are formulated on the basis of the analysis of modern definitions of enterprise competitiveness. It is said that the ultimate judge of competitiveness is the market, but other factors also play an essential role. These include innovativeness, time, word-of-mouth marketing and the need to build durable advantage that can’t be replicated.